Mixture toxicity effects of sea louse control agents in Daphnia magna. (February 2016) - Rose, Stephanie; Altenburger, Rolf; Sturm, Armin
Abstract: Caligid sea lice are ectoparasites causing major disease problems in industrial salmon farming. Sea louse control currently relies widely on parasiticides. Among non-target species, crustaceans are particularly susceptible to salmon delousing agents. Drug combinations have recently been suggested for sea louse control; however, no information is available on the non-target effects of such mixtures. To obtain first insights into combination effects of salmon parasiticides, acute toxicity tests with the crustacean model species Daphnia magna were conducted. Four compounds, including two organophosphates and two pyrethroids, were tested individually and in all pair-wise combinations at one fixed concentration ratio. For most combinations, observed toxicities were close to predictions assuming concentration additivity. However, deltamethrin and cypermethrin showed greater than predicted combination effects, while the inverse was observed for deltamethrin and malathion. The results demonstrate combination effects of anti-sea louse agents and suggest that predictions based on concentration additivity are in most cases protective. Highlights: We investigated the acute toxicity of mixtures of anti-sea louse in Daphnia magna . Two organophosphates and two pyrethroids were studied in all binary combinations. Observed mixture effects were in most cases close to predictions based on concentration additivity.